Identification and Characterization of the LecRLKs Gene Family in Maize, and Its Role Under Biotic and Abiotic Stress - Xiangbo Yang; Ziqi Chen; Jianyu Lu; Xuancheng Wei; Yanying Yao; Wendi Lv; Jiarui Han; Jianbo Fei (Biology)
Plant lectin receptor-like kinases (LecRLKs) are plant membrane protein receptor kinases. Lectin-like receptor kinases play a crucial role in regulating plant growth, development, and responses to environmental stimuli. It can rapidly respond to both biotic and abiotic stresses while mediating mechanisms of plant immune responses. This study represents the first identification of the LecRLK family genes in maize. It analyzes the gene structure, chromosomal locations, phylogenetic classification, promoter homoeotropic elements, and expression patterns under both biotic and abiotic stresses. The results indicate that these genes possess kinase and transmembrane domains, along with specific L-type or G-type extracellular domains. Most ZmLecRLK gene promoters contain cis-acting elements that are responsive to known hormones and stressors. Furthermore, these genes have been identified as being sensitive to both biotic and abiotic stresses. This discovery establishes a significant theoretical foundation for the selection of corn varieties in adverse environments. Additionally, it provides a basis for further in-depth exploration of the molecular regulatory mechanisms of LecRLK family genes.